Screening of HIV-1 Protease Using a Combination of an Ultra-High-Throughput Fluorescent-Based Assay and RapidFire Mass Spectrometry. (June 2015) - Meng, Juncai; Lai, Ming-Tain; Munshi, Vandna; Grobler, Jay; McCauley, John; Zuck, Paul; Johnson, Eric N.; Uebele, Victor N.; Hermes, Jeffrey D.; Adam, Gregory C.
HIV-1 protease (PR) represents one of the primary targets for developing antiviral agents for the treatment of HIV-infected patients. To identify novel PR inhibitors, a label-free, high-throughput mass spectrometry (HTMS) assay was developed using the RapidFire platform and applied as an orthogonal assay to confirm hits identified in a fluorescence resonance energy transfer (FRET)–based primary screen of > 1 million compounds. For substrate selection, a panel of peptide substrates derived from natural processing sites for PR was evaluated on the RapidFire platform. As a result, KVSLNFPIL, a new substrate measured to have a ~ 20- and 60-fold improvement in k cat / K m over the frequently used sequences SQNYPIVQ and SQNYPIV, respectively, was identified for the HTMS screen. About 17% of hits from the FRET-based primary screen were confirmed in the HTMS confirmatory assay including all 304 known PR inhibitors in the set, demonstrating that the HTMS assay is effective at triaging false-positives while capturing true hits. Hence, with a sampling rate of ~7 s per well, the RapidFire HTMS assay enables the high-throughput evaluation of peptide substrates and functions as an efficient tool for hits triage in the discovery of novel PR inhibitors.